Analysis of Rainfall Trend in Benin and Warri Cities of Southern Nigeria - Emeka-Chris , C. C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
In this study the trends and patterns in the rainfall of Benin and Warri cities in Southern Nigeria were examined. Rainfall data (1983-2014) for Benin and Warri cities were used. The mean, standard deviation, coefficient of skewness, coefficient of kurtosis, coefficient of variation and standardized anomaly index were used as statistical tools to analyze the data and establish the distribution of rainfall in these cities.  SPSS 17 and Minitab 16 were used to analyse the data the data obtained.  The result of the trend analysis revealed that the year 2005 recorded the lowest annual rainfall of 229.10mm and 1925.8mm for Benin and Warri respectively. The years 2008 and 2011 recorded the highest rainfall of 4489.8mm and 3068.70mm for Warri and Benin respectively. The mean annual rainfall for the study period was 2162.46mm. The   annual rainfall trend indicated a progressive increase in the annual rainfall during the period of study.  The implications are that 2011 and 2008 recorded the highest rainfall event, including heavy rainfall, that can lead to flooding for Benin and Warri respectively while 2005 recorded the lowest rainfall events that can lead to drier year, potentially affecting crop yield in both cities. It is recommended that water resources managers should make adequate arrangement on how to prevent flooding by designing and constructing water carrying structures, including adequate urban and regional planning.